2020
DOI: 10.1016/j.bpsc.2019.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Report on the Effects of a Low Dose of LSD on Resting-State Amygdala Functional Connectivity

Abstract: The practice of "microdosing", or the use of repeated, very low doses of LSD to improve mood or cognition, has received considerable public attention, but empirical studies are lacking. Controlled studies are needed to investigate both the therapeutic potential and the neurobiological underpinnings of this pharmacologic treatment. Methods. The present study was designed to examine the effects of a single low dose of LSD (13 micrograms) vs placebo on resting-state functional connectivity and cerebral blood flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(102 citation statements)
references
References 37 publications
8
93
1
Order By: Relevance
“…17 Interestingly, although having negligible subjective effects, 13 µg LSD tartrate (equivalent to 10 µg LSD base) has been shown to alter brain connectivity in the limbic system. 18 These data indicate that healthy subjects begin to subjectively perceive effects of LSD at a threshold dose of 10 µg LSD base. Thus, doses < 10 µg LSD base could be considered subperceptual and would qualify as "microdoses."…”
Section: Discussionmentioning
confidence: 80%
“…17 Interestingly, although having negligible subjective effects, 13 µg LSD tartrate (equivalent to 10 µg LSD base) has been shown to alter brain connectivity in the limbic system. 18 These data indicate that healthy subjects begin to subjectively perceive effects of LSD at a threshold dose of 10 µg LSD base. Thus, doses < 10 µg LSD base could be considered subperceptual and would qualify as "microdoses."…”
Section: Discussionmentioning
confidence: 80%
“…The increase in connectivity was related to the changes in positive mood, measured by the Positive and Negative Affect Schedule (PANAS). 49 Study in patients with anxiety. Gasser and colleagues investigated the safety and efficacy of LSD-psychotherapy in patients with anxiety related to life-threatening diseases.…”
Section: Older Research With Lsdmentioning
confidence: 99%
“…While this (microdosing) psychedelics research field is still in its infancy, preliminary findings indicate that low doses of both LSD and psilocybin affect assessed biological processes. 30,38 A first study showed changed connectivity in brain areas involved in affective behaviour, after a single dose of LSD (13 mcg tartrate, p.o.). Interestingly these changes were also related to positive mood effects, 38 which suggests this might be a potential mechanism underlying alleged therapeutic effects in depression.…”
Section: The Cause Of Effects: Expectancy and Underlying Biologymentioning
confidence: 99%
See 2 more Smart Citations